Given the equation 4x + 7 = 3(2x − 5), solve for the variable. Explain each step and justify your process.
B.Sam solved a similar equation below. Is Sam's solution correct? Explain why or why not.
5x − 1 = 2(x + 4)
5x − 1 = 2x + 8
7x − 1 = 8
7x = 7
x = 1

Respuesta :

Part 1: [tex]4x + 7 = 3(2x - 5)[/tex] 

[tex]4x+7=6x-15[/tex] 

[tex]7=6x-15-4x [/tex] 

[tex]7=2x-15[/tex] 

[tex]7+15=2x[/tex] 

[tex]22=2x[/tex] 

[tex]22=2x / 2[/tex] 

[tex]x=11[/tex] 

Part 2: Sam is not correct because he messed up the second step. He added 2x on both sides to get 7x, instead he should have subtracted.